Pembelajaran Literasi Sains Melalui Pemanfaatan Lingkungan - Reny Kristyowati; Agung Purwanto (Program Studi Pendidikan Guru Sekolah Dasar, Universitas Kristen Satya Wacana, 2019)
The development of science and technology that caused by 21st century development, requires a globally qualified, reliable, and competitive human resources. One of the skills required in 21st century is scientific literacy. Scientific literacy is a skill to use knowledge, identify question, and take conclusion based of evidences for understanding and making decision about nature and changes done to nature by human activities. Scientific literacy in schools can be created and developed by environment utilization. Students observe and do simple scientific activities, they can directly interact and utilize the environment as learning material. By directly learning and observing in nature, scientific literacy learning can be optimalized. The aim of this research are to understand the implementation of scientific literacy learning by utilizing environment and knowing environment’s benefits in developing students’ scientific literacy skill. The methods used are literature review by analyzing sources related to this research. The results found by conducting a literature study showing that by utilizing the environment in scientific literacy learning, student learning outcomes increased. Students are active in learning activities and better understand the scientific literacy learning because it is close to the surrounding environment. It can be concluded that the use of the environment is appropriate for scientific literacy learning.